Investigation of genuine and fake malaya historical banknotes using video spectral comparator and chemometric techniques - Rosli, Nur Deanna (Universiti Sains Malaysia, 2016)
Investigation on banknote authentication is an interesting subject in forensic document examination. The existence of counterfeit banknote in line with their circulation in the market could badly impact the economy of a country. Historical banknotes which are artefacts and considered as collectible items are prone to counterfeiting with advanced printing technology today. Thus, this study aims to help in reducing and prevent fraud crime through discrimination of genuine and fake historical banknotes by VSC and chemometric techniques. In this study, old Malaya money which was Banana notes since the Japanese era were used. Simulated samples were produced using four different printing techniques namely HP Laser, Compaq inkjet, Ricoh photocopy and commercial CDH printing. Both genuine and simulated samples were compared using Leica stereomicroscope and VSC under different light sources. Observation under stereomicroscope showed a better printing quality produced on the genuine samples as compared to all simulated samples. Under different light sources by VSC, all samples showed different reaction towards different light sources. PPMC and PCA were conducted on chromaticity data (colour measurement) generated by VSC during spectral analyse. For PPMC, CDH printing, HP Laser and Ricoh photocopy produced ink colour of high correlation with the ink colour of genuine samples. PCA results revealed that banknotes printed at commercial printing house, CDH were clustered in a closer vicinity to genuine notes. Additionally, PCA also showed good clustering of samples with most of the banknotes are grouped according to their printing methods. In conclusion, genuine and fake historical banknotes could be discriminated using VSC and chemometric techniques, contributing positively to detect fraud crime, especially when dealing with this kind of artefact.